2018
DOI: 10.1242/jeb.167775
|View full text |Cite
|
Sign up to set email alerts
|

Auditory neural networks for attention prefer biologically significant sounds and exhibit sexual dimorphism in anurans

Abstract: Allocating attention to biologically relevant stimuli in a complex environment is critically important for survival and reproductive success. In humans, attention modulation is regulated by the frontal cortex, and is often reflected by changes in specific components of the event-related potential (ERP). Although brain networks for attention modulation have been widely studied in primates and avian species, little is known about attention modulation in amphibians. The present study aimed to investigate the atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(90 reference statements)
0
1
1
Order By: Relevance
“…However it is noteworthy that the present results differ from our previous study showing a sexually dimorphic lateralized attention modulation network in Emei music frogs using Granger causal connectivity analysis, i.e. Granger causal connections in the left telencephalon are stronger in males while those in the right telencephalon are stronger in females (Xue et al, 2018). This difference might reflect species differences.…”
Section: Discussioncontrasting
confidence: 99%
“…However it is noteworthy that the present results differ from our previous study showing a sexually dimorphic lateralized attention modulation network in Emei music frogs using Granger causal connectivity analysis, i.e. Granger causal connections in the left telencephalon are stronger in males while those in the right telencephalon are stronger in females (Xue et al, 2018). This difference might reflect species differences.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, the frontal cortex may play an important role in auditory attention modulation in humans, non-human primates and rodents [ 79 , 80 , 81 ], while birds also have similar structures involved in attention regulation [ 82 ]. Correspondingly, our previous study found that the telencephalon might play a similar role in attention regulation in music frogs as the frontal cortex did in mammals [ 83 ]. Therefore, it seems reasonable to speculate that similar auditory attention mechanisms (voluntary attention vs. reflexive attention) may be widespread in vertebrates.…”
Section: Discussionmentioning
confidence: 76%